Evaluating the Safety Effects of Span Wire to Mast Arm Signal Conversion. Issue 30 (December 2018) - Khattak, Zulqarnain H.; Fontaine, Michael D.
The mast arm signal mounting configuration has often been assumed to provide greater conspicuity and visibility than span wire installations, but the impacts of this countermeasure on road safety have not been well established quantitatively. This paper's intent is to provide a comprehensive evaluation of safety effects of converting span wire installations to mast arm installations. An Empirical Bayes before–after safety analysis was conducted using crash data for 30 intersections collected from the Virginia Department of Transportation (VDOT). A crash type analysis was also conducted to observe changes in crash types. Based on the data available, no statistically significant improvement in safety was found. Average crash modification factor (CMF) values of 0.97 and 0.98 were observed for total and fatal and injury crashes, but these CMFs were not statistically significant. A reduction in the proportion of angle crashes was observed, but the change was not statistically significant and the overall distribution of crashes did not change significantly after converting signal configurations from span wire to mast arm. Although mast arm deployments may offer advantages in maintenance costs and aesthetics, there does not appear to be a substantial safety benefit to these conversions.